Large Section of Soft Rock Gob-Side Entry Retaining Surrounding Rock Control - Xizhi Wang; Yongjian Zhu; Ping Wang; Heng Ren; Peng Li; Xianwen He; Jianhua Lv (Advances in Civil Engineering)
When cutting roof and pressure relief, the impact of blasting is especially obvious on the integrity of the roof of a large-section soft-rock roadway. The reasonable parameters of blasting roof cutting were studied through using Xiaohezui coal mine -12110 roadway as the engineering background. The LS-Dyna simulation results show that: Interval blasting is beneficial to the expansion of interhole cracks and the damage to the perimeter of the hole is smaller than that of adjacent blasting, the lower the charge uncoupling factor, the larger the perimeter of the hole fragmentation zone. The mechanical model of the large-section soft-rock roadway after retrieval was established, the support resistance equation of the roadway side support and the gangue in the extraction area was derived, and the minimum support force required for the roadway side support was solved. According to the site situation, the roadway support scheme for different areas was proposed, and after continuous delamination monitoring of the roof plate, it was found that the amount of roof-plate delamination was finally stabilized within 180 mm after the working face was advanced, and the effect of leaving the roadway was good.